A new short questionaire of fatigue: Relationships with performance and training in elite swimmers - Atlaoui, D.; Lacoste, L.; Barale, F.; Guezenne, Y. C.; Chatard, J. C. (2002)
Intense training has been shown to be associated with mood state disturbances in swimmers The profile of mood state questionnaire (POMS), which includes 65 items, is the most commonly used (McNair et al.; 1992). It has been reported to be an effective marker of the training stress. However this questionnaire is rather long. hence, the aim of the present investigation was to validate an abbreviated 8-item questionnaire of fatigue in elite swimmers, to easily monitor training stress.